The string - Breakey, Caleb Jennings, 1986- (Revell, 2019)
A sociopath is running a deadly social experiment on a university campus. Markus Haas is the first to refuse to play the game. What unravels is a sequence of impossible decisions and a race against time to stop the sociopath before others pay the ultimate price.